Endogeneity and causal attributions in management research: Some reflections and proposals - Giarratana, Marco (Wiley, 2024)
This article explores the pivotal role of causal identification in the domain of management research and its alignment with theory creation. It seeks to stimulate thought about how researchers can approach theories and their causal identification with a review of the canonical methods. The article first addresses the intricacies of identification and the principal methodologies that researchers have recently employed in their investigations. Subsequently, it delves into the inherent costs associated with identification, specifically the need for additional assumptions, and the potential constraints on generalizability. It also promotes a more thoroughly examination of the nature of endogeneity. Finally, it explores how the link between causal identification and theory legitimacy could generate superstitious trajectories.
Keywords: Casuality; Endogeneity; Management research; Theory; 53 Ciencias Económicas::5311 Organización y dirección de empresas; ODS 9 - Industria, innovación e infraestructura